2020
DOI: 10.1101/2020.07.15.203307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying differences in gait adaptability across various speeds using movement synergy analysis

Abstract: IntroductionThe aim of this study was to identify movement synergies during normal-walking that can differentiate healthy adults in terms of gait adaptability at various speeds. To this end, the association between movement synergies and lower-limb coordination variability or Deviation Phase (DP) was investigated. A secondary aim of this study included an investigation into the moderating effect of these movement synergies on the relationship between DP and the smoothness of arm-swing motion quantified as the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Interdependencies between such gait balance control strategies relevant to step-to-step transitions (i.e. push-off modulation, lateral ankle and foot placement mechanisms) have been identified in the literature (17,57). The interdependencies between lateral ankle and foot placement mechanisms were found to be consistent with varied perturbation direction, however only a weak association with the push-off mechanism was found.…”
Section: Open-and Closed-loop Control Of Whole-body Angular Momentummentioning
confidence: 90%
See 2 more Smart Citations
“…Interdependencies between such gait balance control strategies relevant to step-to-step transitions (i.e. push-off modulation, lateral ankle and foot placement mechanisms) have been identified in the literature (17,57). The interdependencies between lateral ankle and foot placement mechanisms were found to be consistent with varied perturbation direction, however only a weak association with the push-off mechanism was found.…”
Section: Open-and Closed-loop Control Of Whole-body Angular Momentummentioning
confidence: 90%
“…A leave-one out cross-validation revealed that the first 4 PMk did not change by >15° and these were deemed valid (34). The first PM explaining 61.7% of the overall variance was chosen for further analysis only as this primary PM has been identified in previous studies as the basic inverted-pendulum motion of gait and as such is of specific relevance to this study's aims (17,42). With this primary PM the number of zero-crossings in its corresponding PAk time-series were counted for each participant (34,36), thus formulating the independent variable Nk for further analysis.…”
Section: Independent Variable Computationmentioning
confidence: 99%
See 1 more Smart Citation